The psychosocial impact of serological herpes simplex type 2 testing in an urban HIV clinic. Issue 4 (1st August 2005) - Meyer, J L; Crosby, R A; Whittington, W L H; Carrell, D; Ashley-Morrow, R; Meier, A S; Harrington, R D; DiClemente, R; Wald, A
Abstract : Background/objectives: Herpes simplex virus type 2 (HSV-2) is a common infection among HIV infected people. HSV type specific serologies permit the diagnosis of previously unrecognised HSV-2 infection. While substantial psychosocial morbidity has been associated with a clinical diagnosis of genital herpes, the burden associated with a serological diagnosis of HSV-2 is unclear. This study prospectively measured the psychosocial response to a new serological HSV-2 diagnosis in patients receiving care at an urban HIV clinic. Methods: At entry, sera were tested for HSV-1 and HSV-2 antibodies by western blot. Participants completed a 90 item psychosocial and life quality questionnaire at enrolment, and at 2 weeks, 3 months, and 6 months after receiving test results. Results: Of 248 HIV infected participants, 172 (69.4%) were HSV-2 seropositive and 116 (67.4%) seropositive people did not have a previous history of genital herpes. After correction for multiple comparisons, no statistically significant differences were detected on the psychosocial and life quality scales between those who received a new HSV-2 serological diagnosis compared with those who were HSV-2 seropositive with a history of genital herpes, or those who tested HSV-2 seronegative. Additionally, no significant changes in scores were observed during follow up. Conclusions: HSV-2 was a common but often unrecognised infection in this urban HIV clinic and participants coped well with a positive HSV-2 result. Concerns about psychosocial burden should not deter serological testing for HSV-2. Given the epidemiological and clinical interaction between HSV-2 and HIV, these data support routine HSV-2 testing of HIV infected people.